1991
DOI: 10.1677/joe.0.1280071
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 11,13-dihydroxy-14-octadecaenoic acid as a circulating Na+/K+-ATPase inhibitor

Abstract: Two digitalis-like compounds (DLC) were purified to homogeneity from bovine plasma. The purification procedure consisted of organic extractions and batch chromatography followed by three subsequent separations using reverse-phase high-performance liquid chromatography. The presence of a DLC in the different fractions was monitored by their ability to inhibit (a) [3H]ouabain binding to rat brain synaptosomes, and (b) microsomal Na+/K(+)-ATPase activity. Using mass spectrometry and nuclear magnetic resonance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is suggested that the material present in the lens and responsible for the digitalis-like activity is mainly 19-norbufalin and a peptide-(Thr-Gly-A1a)-conjugated 19-norbufalin ( Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that the material present in the lens and responsible for the digitalis-like activity is mainly 19-norbufalin and a peptide-(Thr-Gly-A1a)-conjugated 19-norbufalin ( Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of ['Hlouabain to a rat brain synaptosomal fraction was carried out by a conventional filtration technique as previously described [19]. In brief; the reaction mixture (500 p1 final volume) contained the following constituents (final concentrations); SO mM Tris/HCI, pH 7.4,0.4 mM EDTA, 80 mM NaC1,4 mM MgS04, 2 mM ATP (Tris, vanadium free), ['Hlouabain (32 nM, 19.5 Ci/mmol; New England Nuclear) and other additions as indicated.…”
Section: Inhibition Of [3h]ouabain Bindingmentioning
confidence: 99%
See 2 more Smart Citations